MON-443 SPECT/CT Localization of Incidental Diverticular Bleed After Radioiodine (i(131)) Therapy for Metastatic Thyroid Cancer - Doshi, Sejal B (J Endocr Soc, 2020)
Background: Radioiodine therapy for patients with metastatic papillary and follicular thyroid cancer status post total thyroidectomy improves overall survival and is standard of care. Physiologic and pathologic biodistribution of I(131) is dependent on tissue sodium iodine symporter expression with nonspecific radioiodine distribution seen secondary to physiologic routes of excretion. Clinical Case: Whole body scintigraphy (WBS) was performed seven days after I(131) therapy in a 37-year-old male treated for metastatic papillary thyroid cancer with extension to a thyroglossal duct cyst at the time of surgery. His post-procedural course was uncomplicated with the exception of self-limited hematochezia six days after ablation. WBS images demonstrated a focus more superiorly in the neck concordant with metastatic thyroglossal duct cyst involvement. Activity was also present in the small and large bowel distribution reflecting normal routes of radioiodine excretion. WBS images depicted a discrete focus of radioiodine activity in the right lower quadrant, which SPECT/CT further localizes as activity in the sigmoid colon. Non-contrast CT images demonstrate an associated linear pattern of hyperdense hyperattenuation in the colonic lumen consistent with fresh blood. It is well established that the physiologic and pathologic biodistribution of I(131) is dependent on tissue sodium-iodine symporter expression with additional distribution secondary to normal routes of excretion. Nonspecific radioiodine localization has been described at sites of inflammation secondary to vasodilation and increased vascular permeability resulting in leakage and accumulation in tissues. Sodium-iodine expression is found in many tissues, including salivary glands, lactating mammary glands, gastric mucosa, thymus, and small bowel; however, they are not expressed in the colon, nasopharyngeal mucosa, or orbital fibroblasts. I(131) localization has been previously described within numerous body diverticula, such as Zenker’s and Meckel’s diverticula; however, radioiodine activity in association with an acute colonic diverticular bleed has not been reported. Conclusion: We propose that the isolated focus of radioiodine activity in the sigmoid colon associated with transient self-limited bleed could be either related to preexisting diverticulitis leading to I(131) accumulation secondary to hyperemia, increased vascular capillary permeability, and subsequent aggravation of colonic mucosa resulting in a transient bleed or due to incidental nonspecific pooling of radioiodine in a colonic diverticulum resulting in secondary mucosal irritation with subsequent minor bleeding. To our knowledge this is the first reported case of SPECT/CT localization of radioiodine to an isolated colonic diverticular bleed in a patient status post I(131) therapy for metastatic papillary thyroid cancer.